Morphology and protrusionretraction of the female genital chamber of Phyllophaga obsoleta (Coleoptera: Melolonthidae) - Romero-López, A.A; Arzuffi, R.; Valdez, J.; Morón, M. A. (Instituto de Ecología, A.C., 2009)
The females of Phyllophaga obsoleta (Blanchard) (Coleoptera: Melolonthidae) have a great agricultural importance in Mexico. They display a sexual calling behavior, that expose a bag-like structure on the abdominal tip, wich causes them to attract the males. The content of this structure has been extracted and confirmed his biological activity by wind tunnel and electroantenography bioessays. Nevertheless, their morphologic characteristics have not been studied yet. For that reason in the present study, the P. obsoleta abdominal terminalia were characterized morphologically and protrusion-retraction mechanism of bag-like structure was studied. Longitudinal dissections of the abdominal terminalia were analyzed with stereoscopic microscopy. The bag-like structure is the protractile genital chamber (PGC) of Melolonthidae females and its protrusion and retraction is related to the activity of lateral sterno-sacular muscles with ventral sterno-sacular muscles, as well as for intersegmental membranes VIII and IX. They should be involucrated in protrusion and retraction PGC mechanisms